The rapid correction of hypercalcemia at presentation of acute lymphoblastic leukemia using high-dose methylprednisolone - Unal, Sule; Durmaz, Erdem; Erkoçoğlu, Mustafa; Bayrakçi, Benan; Bircan, Ozlem; Alikaşifoğlu, Ayfer; Cetin, Mualla (The Turkish Journal of Pediatrics, 2008)
Hypercalcemia is a well-recognized complication of neoplastic disorders. Herein, we report a hypercalcemic pediatric acute lymphoblastic leukemia case at presentation refractory to hydration, furosemide, pamidronate and calcitonin. Normal serum calcium levels were achieved with the initiation of chemotherapy protocol including vincristine, daunomycin and high-dose methylprednisolone. The impact of high-dose methylprednisolone in the correction of severe hypercalcemia in steroid-responsive tumors as an initial treatment approach or for cases refractory to other measures may be life-saving.